2012
DOI: 10.1002/brb3.107
|View full text |Cite
|
Sign up to set email alerts
|

Social exclusion, infant behavior, social isolation, and maternal expectations independently predict maternal depressive symptoms

Abstract: The objective of the study was to identify latent variables that can be used to inform theoretical models of perinatal influences on postnatal depressed mood and maternal–infant attachment. A routine survey of mothers with newborn infants was commenced in South Western Sydney in 2000. The survey included the Edinburgh Postnatal Depression Scale (EPDS) and 46 psychosocial and health-related variables. Mothers (n = 15,389) delivering in 2002 and 2003 were surveyed at 2–3 weeks for depressive symptoms. Nonlinear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 44 publications
6
41
0
1
Order By: Relevance
“…Social cohesion and its related concepts of social networks and social capital have a positive influence on families and maternal depression. The voices of mothers, practitioners, and our quantitative analysis Eastwood, Jalaludin, Kemp, Phung, Barnett, & Tobin, 2012), all suggest the protective influence of support and social integration. Global forces are increasing the migration of peoples of different ethnic and cultural backgrounds to South West Sydney.…”
Section: Neighborhood and Macro-arena Analysismentioning
confidence: 79%
See 1 more Smart Citation
“…Social cohesion and its related concepts of social networks and social capital have a positive influence on families and maternal depression. The voices of mothers, practitioners, and our quantitative analysis Eastwood, Jalaludin, Kemp, Phung, Barnett, & Tobin, 2012), all suggest the protective influence of support and social integration. Global forces are increasing the migration of peoples of different ethnic and cultural backgrounds to South West Sydney.…”
Section: Neighborhood and Macro-arena Analysismentioning
confidence: 79%
“…The study reported here is part of a critical realist mixed method multilevel study that seeks to identify and explain complex perinatal contextual social and psychosocial mechanisms that may influence the developmental origins of health and disease with a focus on the role of postnatal depression . The main study used various qualitative and quantitative methods, including emergent qualitative analysis , 2015, non-linear principal component (Eastwood, Jalaludin, Kemp, Phung, Barnett, & Tobin, 2012) and exploratory factor analysis (Eastwood, Jalaludin, Kemp, & Phung, 2014b), visualization and cluster analysis (Eastwood, Jalaludin, Kemp, Phung, & Adusumilli, 2013), and Bayesian ecological and multilevel exploratory spatial analysis , 2014aEastwood, Jalaludin, Kemp, Phung, & Barnett, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…, Eastwood et al . ). There were no differences in age of residential area for social capital and social support measures; however, those who lived in newer areas (<10 years) scored higher means for mental well‐being.…”
Section: Discussionmentioning
confidence: 97%
“…, Eastwood et al . ), disadvantaged mothers of children aged 0‐4 years with depressive symptoms (Mulvaney & Kendrick ) and for mental and physical well‐being more broadly (Berkman & Glass ). Perceived social support is commonly viewed and measured as functional forms: information, instrumental, emotional and appraisal (House et al .…”
Section: Introductionmentioning
confidence: 99%
“…A non-linear principal component and regression analysis identified that social exclusion, infant behaviour, migrant social isolation and maternal expectations independently predicted postnatal maternal depressive symptoms [25]. Our suburb-level spatial studies identified clustering of postnatal depression in regions known to be socially disadvantaged and with high rates of migrant mothers (Figure  1) [26].…”
Section: Introductionmentioning
confidence: 95%